Office-Based Post–Axial Polydactyly Excision in Neonates, Infants, and Children. Issue 2 (February 2016) - Carpenter, Christopher L.; Cuellar, Trajan A.; Friel, Michael T.
Abstract : Background: In adult hand surgery literature, there are multiple publications highlighting the successful use of office-based hand surgery in the treatment of hand conditions. There are few instances of office-based hand surgery in the pediatric population present in the literature. Polydactyly of the hand is one of the most common congenital hand malformations. The authors present a case series of successfully performed in-office surgical excision of the type B postaxial polydactylous digit in infants and children. The added health care utilization improvements by performing this in the office, as well as lack of exposure to general anesthesia are reviewed. Methods: A retrospective review of the patients treated was completed and the technique of in-office excision documented. Results: Over a 15 month period, a total of twenty-six children were treated in the office for postaxial polydactyly. The average age of the child at the time of excision was 3.3 months old, with a median of 1.4 months with a range of 9 days–4.2 years. There were no postprocedure complications in function or sensation. Conclusions: The authors report a case series of successful surgical excision of type B postaxial polydactyly in newborns, infants, and children in an office setting with the use of lidocaine with epinephrine. This technique is a cost-conscious approach to the condition without the need for general anesthesia. This demonstrates excellent results with improved safety without sacrificing quality. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Coding Perspective for this Article is on Page 567.